Effectiveness of Gender Policy in Indonesia: A Review of the Achievement of Sustainable Development Goals (SDG’s) - Bilqista , Aulia Noka; Setijaningrum, Erna (Journal of Social and Policy Issues, 2025)
This study aims to analyze the effectiveness of public policies in addressing gender issues as part of efforts to achieve the Sustainable Development Goals (SDG's) in Indonesia. The research method used is a descriptive qualitative approach based on a literature review. Research data were obtained from monitoring policy implementation supported by statistical data, which were analyzed using the VOSviewer application. The results of the study indicate that although the government has taken various positive steps in formulating and implementing gender policies, there are still significant challenges in translating these policies into fundamental changes in society. These obstacles include patriarchal cultural norms, lack of understanding of officials and the community regarding gender policies, and limited active participation of the community, especially women. This study confirms that active community participation and increasing women's social awareness are important factors that determine the sustainability and success of gender policy implementation. The conclusion of this study emphasizes the need for continuous improvement steps in public policy to address gender-based issues more effectively. Improving monitoring and evaluation mechanisms on an ongoing basis, as well as active involvement from all levels of society, including the government, non-governmental organizations, and local communities, are considered very important in realizing the vision of gender equality and achieving the SDG's in Indonesia. Thus, this study makes an essential contribution to deepening the understanding of gender policy dynamics in the context of sustainable development and offers strategic recommendations for strengthening future policies.